PENGARUH TRANSAKSI INTERNET BANKING TERHADAP KEPUASAN NASABAH BANK BRI TANAH ABANG JAKARTA PUSAT - Putri Sarirati; Rengga Abdi Yuri Aprianda (Aliansi : Jurnal Manajemen dan Bisnis, 2023)
The purpose of this research is: "To find out the Effect of Internet Banking Transactions on Customer Satisfaction at Bank BRI Tanah Abang, Central Jakarta."This study uses a quantitative approach using descriptive and associative research types. The population in this study were 5 respondents to customers of Bank BRI Tanah Abang, Central Jakarta. In this study, the number of samples was determined using a saturated sampling formula. So that the sample used was 5 respondents at Bank BRI Tanah Abang, Central Jakarta.The results of this study indicate that: There is an influence of Internet Banking Transactions (X) on Customer Satisfaction (Y), with the tcount obtained for Internet Banking Transactions (X) of 9,962, while the ttable value for n = 75 is 6,349, while the ttable value for N = 75 of 1,992. So 6.349 1.992, then H0 is rejected and Ha is accepted. As for the R Square value of 0.356. This shows that 35.6% of Internet Banking Transactions (X) have an effect on Customer Satisfaction (Y), while the remaining 64.4% are influenced by other factors not examined in this study.